‘Most at risk’ for COVID19? The imperative to expand the definition from biological to social factors for equity - Afifi, Rima A.; Novak, Nicole; Gilbert, Paul A.; Pauly, Bernadette; Abdulrahim, Sawsan; Rashid, Sabina Faiz; Ortegae, Fernando; Ferrand, Rashida A. (Elsevier, 2022)
This article was published in Elsevier [ © 2020 Elsevier Inc. All rights reserved.] and the definite version is available at: https://doi.org/10.1016/j.ypmed.2020.106229 The Journal's website is at: https://www.sciencedirect.com/science/article/abs/pii/S009174352030253X?via%3Dihub